Mycoplasma pneumoniae‐associated mucositis complicated by herpes simplex virus dissemination and Staphylococcus Epidermidis bacteremia. Issue 4 (5th June 2020) - Agnihotri, Gaurav; Loucks, Emily; Ashack, Kurt; Tsoukas, Maria
Abstract: Prominent mucositis with minimal or no cutaneous involvement in the setting of Mycoplasma pneumoniae infection describes a clinical entity recently termed Mycoplasma‐ induced rash and mucositis (MIRM). About 81% of patients with MIRM experience complete resolution; however, the disease course in approximately 11% of patients is complicated by mucosal sequelae. We describe a patient with MIRM complicated by HSV dissemination and Staphylococcus epidermidis bacteremia and outline the management of mucocutaneous eruptions without systemic immunosuppressant agents.